(untitled) (Research, Society and Development, 2021)
This work develops discussions on the continuing education of teachers in the early years who teach mathematics, more specifically on the concept of multiplication and division. It presents master’s research data, produced in a training action carried out in 2017, with 17 public school teachers (municipal and state). In theoretical and methodological terms, the investigation is linked to the assumptions of Historical-Cultural Theory and the principles of dialectical historical materialism. Based on these references, we seek to understand the phenomenon of training as a movement of transformation, where the appropriation of knowledge, in a collective perspective, contributes to a new quality of teaching actions in the area of ​​teaching mathematics. Data analysis indicates that the training actions carried out collectively mobilized the interest of the participants and favored the redefinition of the concepts of multiplication and division.